2015
DOI: 10.1007/s11064-015-1671-5
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Roles of Nogo-A in CNS Biology and Diseases

Abstract: Nogos have become a hot topic for its well-known number Nogo-A's big role in clinical matters. It has been recognized that the expression of Nogo-A and the receptor NgR1 inhibit the neuron's growth after CNS injuries or the onset of the MS. The piling evidence supports the notion that the Nogo-A is also involved in the synaptic plasticity, which was shown to negatively regulate the strength of synaptic transmission. The occurrence of significant schizophrenia-like behavioral phenotypes in Nogo-A KO rats also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 156 publications
(256 reference statements)
0
9
0
1
Order By: Relevance
“…Postmortem and genetic studies have implicated Nogo expression levels and its chromosomal location (chromosome 2p16.1) in the etiology of schizophrenia 162526272829. In addition, in chromosome 22q11, which is also associated with schizophrenia, lays the Nogo-66 receptor NgR1 17. It was reported that knockout of the Nogo-A gene could cause specific behavioral abnormalities similar to schizophrenia-related endophenotypes, for instance deficient sensorimotor gating, disrupted latent inhibition, perseverative behavior and increased sensitivity to the locomotor stimulating effects of amphetamine 17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postmortem and genetic studies have implicated Nogo expression levels and its chromosomal location (chromosome 2p16.1) in the etiology of schizophrenia 162526272829. In addition, in chromosome 22q11, which is also associated with schizophrenia, lays the Nogo-66 receptor NgR1 17. It was reported that knockout of the Nogo-A gene could cause specific behavioral abnormalities similar to schizophrenia-related endophenotypes, for instance deficient sensorimotor gating, disrupted latent inhibition, perseverative behavior and increased sensitivity to the locomotor stimulating effects of amphetamine 17.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in chromosome 22q11, which is also associated with schizophrenia, lays the Nogo-66 receptor NgR1 17. It was reported that knockout of the Nogo-A gene could cause specific behavioral abnormalities similar to schizophrenia-related endophenotypes, for instance deficient sensorimotor gating, disrupted latent inhibition, perseverative behavior and increased sensitivity to the locomotor stimulating effects of amphetamine 17. The result of our study with lower serum Nogo-A levels in patients with schizophrenia also supports the previous studies in explaining myelin dysfunction theory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nerve-growth inhibitory ligand Nogo-A was first identified in CNS myelin in 1988 (Caroni and Schwab, 1988a , b ) and later shown to be expressed also in neurons (Chen et al, 2000 ; Josephson et al, 2001 ). Currently, known ligands, receptors, co-receptors, and modulators participating in Nogo-like signaling encompass some 20 proteins (Mironova and Giger, 2013 ; Schwab and Strittmatter, 2014 ; Sui et al, 2015 ; Seiler et al, 2016 ). Together, they regulate development, adult structural synaptic plasticity and memory (McGee et al, 2005 ; Mingorance-Le Meur et al, 2007 ; Giger et al, 2010 ; Akbik et al, 2013 ; Mironova and Giger, 2013 ; Nordgren et al, 2013 ; Schwab and Strittmatter, 2014 ; Karlsson et al, 2016 , 2017 ; Zagrebelsky et al, 2017 ), including appropriate motor learning (Zemmar et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The system also affects recovery from injury, such as axonal regeneration (Chen et al, 2017 ), and is involved in CNS reactions to injury and disease, including multiple sclerosis, schizophrenia, intracerebral tumors and stroke (Eslamboli et al, 2006 ; Cheatwood et al, 2008 ; Jung et al, 2011 ; Xiong et al, 2012 ; Willi and Schwab, 2013 ). Nogo-A can bind to Nogo receptor 1 (NgR1) through an extracellular loop, activating the NgR1 signaling complex (including coreceptors) resulting in nerve growth inhibition via the RhoA pathway, visualized in Figure 1 (Fournier et al, 2001 ; Niederöst et al, 2002 ; Sui et al, 2015 ). The signaling system has grown more complex as exemplified by the fact that Nogo-A can also bind to paired immunoglobulin-like receptor B (PirB), sphingosine-1-phosphate receptor 2 (S1PR2), and Syndecans (GrandPré et al, 2002 ; Atwal et al, 2008 ; Kempf et al, 2014 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%